PENGARUH BUAH DURIAN (DURIO ZIBETHINUS L.) TERHADAP KADAR KOLESTEROL (HDL DAN LDL) DARAH TIKUS PUTIH (RATTUS NORVEGICUS) (LP2MTBM MAKARIOZ, 2023)
Dulrian (Dulrio Zibelthinuls L.) is a frulit that has a high contelnt of nultrielnts and vitamins C &; B, is anti-oxidant, anti-obelsity, anti-cancelr, and anti-cardiovascullar. Elxamination of HDL and LDL cholelstelrol lelvells in thel body is important to do in elvalulating thel helalth of thel body against cardiovascullar diselasel, dulrian has high lelvells of ulnsatulrateld fat, so it can potelntially bel a natulral LDL lowelring for thel body if consulmeld at optimal dosels and also hellps raisel HDL and LDL lelvells an imbalancel can lelad to cardiovascullar diselasel, which is thel highelst killelr diselasel according to WHO. Thel most popullar typel of dulrian in Indonelsia is Dulrio Zibelthinuls L, nativel to thel forelsts of Sulmatra, Malaysia, and Kalimantan. The purpose this research To deltelrminel thel elffelct of giving dulrian frulit flelsh (Dulrio Zibelthinuls L.) against blood cholelstelrol lelvells (HDL and LDL) of whitel rats (Rattuls Norvelgiculs L). Trulel elxpelrimelnt with